RELATIONSHIP BETWEEN FOAMING BEHAVIOR AND SURFACE ENERGY OF ASPHALT BINDER - Jian-ping Xu; Kai Zhang; Yao-ting Zhu (Civil Engineering Journal, 2017)
To solve the problem of insufficiency in microscopic performance of foamed asphalt binder, surface energy theory was utilized to analyze the foaming behavior and wettability of asphalt binder. Based on the surface energy theory, the Wilhelmy plate method and universal sorption device method were employed to measure the surface energy components of asphalt binders and aggregates, respectively. Combined with the traditional evaluation indictor for foamed asphalt, the relationship between the foaming property and surface energy of asphalt binder was analyzed. According to the surface energy components, the wettability of asphalt binder to aggregate was calculated to verify the performance of foamed asphalt mixture. Results indicate that the foaming behavior of asphalt will be influenced by surface energy, which will increase with the decline of surface energy. In addition, the surface energy of asphalt binder significantly influences the wettability of asphalt binder to aggregates. Meanwhile, there is an inversely proportional relationship between surface energy of asphalt binder and wettability. Therefore, it can be demonstrated that surface energy is a good indictor which can be used to evaluate the foaming behavior of the asphalt binder. And it is suggested to choose the asphalt binder with lower surface energy in the process of design of foamed asphalt mixture.